Studies of the Effect of Ionic Strengths on Stability Constants of Co(II) Prolyl-Alanine Complexes - Vighe, D.S.; Sawai, J.T.; Khobragade, B.G.; Narwade, M.L. (Asian Journal of Chemistry, 2010)
The interaction of Co(II) with prolyl-alanine has been studied at various ionic strengths pHmetrically. The values of pK (proton-ligand stability constant) and log K (metal-ligand stability constant) are utilized to estimate the thermodynamic stability constants at various ionic strengths to know the exact nature and mechanism of complexzation equilibria.